Python - Cheng, Christopher; Jackson, Mark (P. Mark) (Somerville, Mass. : Candlewick Press, 2013)
Python wakes in the Australian bush and goes about her day in search of a tasty meal. Includes informative facts about pythons.
Includes index.
Originally published: Newtown, N.S.W. : Walker Books Australia, 2012.
Publisher's Weekly
Publisher's Weekly, January 2013
2.5
K-3.
Keywords: Pythons -- Juvenile fiction; Snakes -- Juvenile fiction; Pythons -- Fiction; Snakes -- Fiction; Pythons -- Fiction; Snakes -- Fiction; Picture books for children